Workshop Pembuatan Infused Water Sebagai Alternatif Minuman Sehat pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Halu Oleo - Windy Rachmayanti Apandi; Nur Satya Maliany; Cantika Alisyah; Ayu Silpina; Dera Kalvio Nita; Devi Savitri Effendy; Febriana Muchtar; Ramadhan Tosepu; Hariati Lestari; Hartati Bahar; Harleli Harleli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Excessive caffeine consumption among university students can lead to negative health effects such as sleep disturbances, anxiety, and dependency. To address this issue, a workshop was conducted to introduce infused water as a healthier alternative to caffeinated beverages among students at the Faculty of Public Health, Halu Oleo University. The program aimed to increase awareness about the benefits of infused water in supporting hydration and energy levels naturally, without caffeine's side effects. The workshop utilized three methods: lectures, practical training, and informational leaflets. Lectures provided insights into the adverse effects of excessive caffeine intake and highlighted infused water's benefits, including improved hydration and detoxification. Practical training allowed participants to create infused water using natural ingredients such as lemon and cucumber, fostering hands-on engagement and encouraging immediate application of the knowledge gained. Leaflets were distributed to reinforce the material and served as a take-home guide for participants to share with others. Evaluation of the program showed a significant improvement in students' knowledge about the health risks of caffeine and their interest in adopting infused water as an alternative. Positive feedback indicated that the materials were informative and practical for daily use. Despite challenges such as limited time for practical demonstrations, the workshop successfully achieved its objectives of promoting healthier beverage choices and equipping students with practical skills to support long-term behavior change. This program demonstrates the potential of integrating educational and interactive methods to encourage healthier lifestyle habits, positioning students as agents of change within their communities.